2021
DOI: 10.5213/inj.2142084.042
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding and Future Perspectives of Interstitial Cystitis/Bladder Pain Syndrome

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic disease characterized by suprapubic pain and lower urinary tract symptoms. Perhaps because of the heterogeneous nature of this disease and its multifactorial etiology, clinical trials in allinclusive populations of IC/BPS patients without phenotyping in the last decade have mainly failed to discover new therapeutic modalities of IC/BPS. Thus, phenotyping IC/BPS, aimed at identifying bladder-centric and/or bladder-beyond pathologies, including cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 43 publications
0
40
0
1
Order By: Relevance
“…18 Furthermore, neovascularization with overexpression of angiogenic factors such as platelet-derived endothelial cell growth factor or vascular endothelial growth factor in the bladder mucosa has been identified as an important mechanism leading to glomerulations in non-Hunner-type IC/BPS. [19][20][21] Therefore, further phenotyping based on mucosal pathologies including angiogenic changes would be necessary to identify those bladdercentric IC patients suitable for intravesical DMSO treatment in the non-Hunner-type IC population. Moderate correlations between GRA and IC symptom variables including ICSI, ICPI, and NRS for bladder pain were observed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Furthermore, neovascularization with overexpression of angiogenic factors such as platelet-derived endothelial cell growth factor or vascular endothelial growth factor in the bladder mucosa has been identified as an important mechanism leading to glomerulations in non-Hunner-type IC/BPS. [19][20][21] Therefore, further phenotyping based on mucosal pathologies including angiogenic changes would be necessary to identify those bladdercentric IC patients suitable for intravesical DMSO treatment in the non-Hunner-type IC population. Moderate correlations between GRA and IC symptom variables including ICSI, ICPI, and NRS for bladder pain were observed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that Hunner‐type IC bladders and a proportion of non‐Hunner‐type IC bladders with severe (grade 3) glomerulations exhibited similarities in terms of decreased urothelial cytoskeleton and cell proliferation protein expression in the bladder epithelium, suggesting a common pathophysiological process in Hunner‐type IC and a subgroup of non‐Hunner‐type IC 18 . Furthermore, neovascularization with overexpression of angiogenic factors such as platelet‐derived endothelial cell growth factor or vascular endothelial growth factor in the bladder mucosa has been identified as an important mechanism leading to glomerulations in non‐Hunner‐type IC/BPS 19–21 . Therefore, further phenotyping based on mucosal pathologies including angiogenic changes would be necessary to identify those bladder‐centric IC patients suitable for intravesical DMSO treatment in the non‐Hunner‐type IC population.…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial cystitis/bladder pain syndrome (IC/BPS) is a chronic condition causing pelvic pain, pressure, or discomfort that is perceived to be related to the urinary bladder, often accompanied by various other urinary symptoms, such as increased urinary urgency and frequency [ 1 , 2 ]. These symptoms present in the absence of infection or other identifiable causes, reflecting the idiopathic nature of the disorder [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Typisch sind neben chronischen Beckenschmerzen, Druck-oder Missempfinden bis hin zu starken Schmerzen im Bereich der Blase auch irritative Beschwerden wie Pollakisurie, Nykturie oder imperativer Harndrang [1]. Neben den offensichtlichen Symptomen können bei einigen IC/BPS-Patienten zusätzlich zystoskopisch und/oder histologisch nachweisbare Veränderungen der Harnblase, die ulzerösen Hunner-Läsionen, auftreten [2,3]. Bis heute ist die Pathogenese weitestgehend ungeklärt und eine Vielzahl an verwechselbaren Erkrankungen machen die interstitielle Zystitis zu einer Ausschlussdiagnose.…”
Section: Introductionunclassified